Highly Porous Carbon Materials from Biomass by Chemical and Carbonization Method: A Comparison Study - Wan Nor Roslam Wan Isahak; Mohamed Wahab Mahamed Hisham; Mohd Ambar Yarmo (Journal of Chemistry)
Porous carbon obtained by dehydrating agent, concentrated sulfuric acid (H2SO4), from biomass containing high cellulose (filter paper (FP), bamboo waste, and empty fruit bunches (EFB)) shows very high surface area and better thermal behavior. At room temperature (without heating), treatment of H2SO4 removed all the water molecules in the biomass and left the porous carbon without emitting any gaseous byproducts. Brunauer-Emmett-Teller (BET) surface analysis has shown that bamboo-based carbon has good properties with higher surface area (507.8 m2/g), micropore area (393.3 m2/g), and better thermal behavior (compared to FP and EFB) without any activation or treatment process. By acid treatment of biomass, it was shown that higher carbon composition obtained from FP (85.30%), bamboo (77.72%), and EFB (76.55%) is compared to carbon from carbonization process. Under optimal sulfuric acid (20 wt.%) uses, high carbon yield has been achieved for FP (47.85 wt.%), bamboo (62.4 wt.%), and EFB (55.4 wt.%).